Wpływ zmiany wartości wskaźnika niezawodności ß wyznaczanego metodą form na ocenę klasy niezawodności RC analizowanej konstrukcji = Impact of the changes in reliability index ß values calculated by the form method for assessment of the reliability class RC of the analyzed structures - Kaliszuk, Joanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents the problem of the invariance of structural reliability analysis results which have been obtained by applying the FORM method, realized by means of HMC simulation. The problem was illustrated by the example of a steel girder analysis for which reliability index values ß (g1) and ß (g2) for identical limit state functions g1 and g2, respectively, were calculated. The paper also illustrates how the differences in the results obtained affect the evaluation of the reliability class RC of the analyzed structure.
Keywords: wskaźnik niezawodności ß; klasa niezawodności RC; metoda FORM (first order reliability method); hybrydowa metoda symulacji Monte Carlo (HMC); metoda elementów skończonych (MES); sztuczne sieci neuronowe (SSN); Reliability Index ß; Reliability Class (RC); First Order Reliability Method (FORM); Hybrid Monte Carlo Method (HMC); Finite Element Method (FEM); Artificial Neural Networks (ANN)